ANALISIS PERILAKU KETIDAKPATUHAN WAJIB PAJAK BADAN (Studi Empirik Pada Kantor Pelayanan Pajak Pratama Jambi) - Nur Kasma Dewi; Junaidi; Salman Jumaili (Magister Ilmu Akuntansi Universitas Jambi, 2016)
This research is replicated from Mustikasari research (2007) and has modified by researcher. This research was conducted to investigate corporate tax non compliance behavior, especially the company of manufacturing industry that was registered in Pratama Tax Office in Jambi. The design of this research was the survey research by using the instrument of the questionnaire. Research using 142 samples of corporate tax payers. The data was analysed using Structural Equation Modeling (SEM) with program AMOS 21.0. The results of hypothesis testing conclude that: (1) attitude toward non compliance behavior on tax professional intention is positive and significant; (2) subjective norm on tax professional intention is positive significant; (3) moral obligation on tax professional intention is positive and significant; (4) perceived behavioral control on tax professional intention is positive and significant; (5) perceived behavioral control on corporate tax non compliance is negative and not significant; (6) tax professional intention on corporate tax non compliance is positive and not significant; (7) perceived of corporate financial condition on corporate tax non compliance is positive and not significant; (8) perceived of corporate facilities on corporate tax non compliance is positive and not significant; (9) perceived of organizational climate on corporate tax non compliance is positive and significant; (10) perceived of Account Representative on corporate tax non compliance is positive and significant.